2001
DOI: 10.1037/0894-4105.15.4.434
|View full text |Cite
|
Sign up to set email alerts
|

Object naming and semantic knowledge in temporal lobe epilepsy.

Abstract: Object-naming impairment is common among temporal lobe epilepsy (TLE) patients, but other aspects of semantic memory have received limited attention in this population. This study examined object-naming ability and depth of semantic knowledge in healthy controls (n = 29) and patients with early onset TLE (n = 21). After administration of the Boston Naming Test (BNT), the authors asked participants to provide detailed definitions of 6 BNT objects. The TLE group demonstrated a significant deficit relative to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
63
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 94 publications
6
63
1
3
Order By: Relevance
“…Broman et al (1997) reported a decline of verbal IQ by 35 points in a child with amnesia after anoxic encephalopathy complicated by bitemporal seizures. Naming deficits have also been reported in adults with temporal lobe epilepsy, suggesting that semantic and episodic memory might be impaired in this condition (Bell et al 2001). Our patient had more general learning difficulties -including short-term memory impairment -than patients with 'developmental amnesia' and also more rapid and pronounced forgetting during episodic memory tasks (Vargha-Khadem et al 2001).…”
Section: Discussionsupporting
confidence: 54%
“…Broman et al (1997) reported a decline of verbal IQ by 35 points in a child with amnesia after anoxic encephalopathy complicated by bitemporal seizures. Naming deficits have also been reported in adults with temporal lobe epilepsy, suggesting that semantic and episodic memory might be impaired in this condition (Bell et al 2001). Our patient had more general learning difficulties -including short-term memory impairment -than patients with 'developmental amnesia' and also more rapid and pronounced forgetting during episodic memory tasks (Vargha-Khadem et al 2001).…”
Section: Discussionsupporting
confidence: 54%
“…This type of naming impairment, known as "pure anomia", has been described as reflecting a disconnection between intact semantic knowledge and phonological word forms (Benson, 1979(Benson, , 1988Damasio et al, 1996;Foundas et al, 1998;Raymer et al, 1997), an assertion that is supported by evidence that word retrieval can be facilitated by phonemic cueing. Naming impairments have also been documented following damage to more anterior (BAs 38,20/21) and medial (BAs 28/34,35/36) temporal lobe regions resulting from a variety of lesion aetiologies, including left anterior temporal lobectomy (Bell et al, 2001;Glosser & D'Onofrio, 2001), herpes encephalitis (Moss, Rodd, Stamatakis, Bright, & Tyler, 2005;Pietrini, Nertempi, Vaglia, Revello, & Pinna, 1988;Schmolck, Kensinger, Corkin, & Squire, 2002;Tyler et al, 2004;Warrington & Shallice, 1984), and semantic dementia (Davies, Graham, Xuereb, Williams, & Hodges, 2004;Hodges, Patterson, Oxbury, & Funnell, 1992a;Lambon Ralph, McClelland, Patterson, Galton, & Hodges, 2001;Mummery et al, 1999;Mummery et al, 2000). In contrast to pure anomia, the pathogenesis of the word retrieval deficit in patients with more anterior left temporal lesions appears to involve degradation of semantic knowledge, manifesting in a high proportion of semantic naming errors (e.g., beaver: chipmunk) and ambiguous or inappropriate circumlocutions.…”
mentioning
confidence: 99%
“…Memory deficit occurs mainly when epilepsy involves both temporal lobes and the dominant hemisphere (9) . These patients may also present with naming problems (10) .…”
mentioning
confidence: 99%